The saponification of lauric acid with calcium soaps as an alternative to in-feed antibiotics in post-weaning piglets (International Journal of Health, Animal Science and Food Safety, 2018)
In the search for the reduction of antibiotics in farm animals, a concept was developed based on studies with medium-chain fatty acid with 6-12 atoms (MCFA). In particular, they have been shown to exhibit against Gram+ bacteria in piglets at relatively high concentrations. However they can be hardly used as such because of their repellent odour and taste and for their rapid absorption in upper gastrointestinal tract. These problems could be overcome by the generation of monoacylglycerol, but esterification is usually carried out on a silica base, which reduces the concentration of FA, therefore limiting the antibacterial effects. Our hypothesis is that the saponification with calcium salts might positively affect their concentration in the GIT. The aim of the present study was to examine the effects of Laurate calcium soap (C12-Ca soap) on growth performance and health of post-weaning piglets. At weaning, 192 crossbreed Topics piglets were assigned to 3 experimental groups consisting of 16 pens (4 pigs/pen each): CTR (negative control), T1 (basal diet plus Amoxycillin at 400 mg/kg), and T2 (basal diet plus C12-Ca soap at 1 kg/ton). Gain and feed consumption did not differ among groups. Feed efficiency was higher in T1 (0,61) and T2 (0,58) than CTR (0,51) (P
Keywords: Piglets; Laurate; Weaning; Antibiotics; Gut health